Imagining the Jew in Anglo-Saxon Literature and Culture - Zacher, Samantha, 1973- (Book collections on Project MUSE., 2016)
"Most studies of Jews in medieval England begin with the year 1066, when Jews first arrived on English soil. Yet the absence of Jews in England before the conquest did not prevent early English authors from writing obsessively about them. Using material from the writings of the Church Fathers, contemporary continental sources, widespread cultural stereotypes, and their own imaginations, their depictions of Jews reflected their own politico-theological experiences. The thirteen essays in Imagining the Jew in Anglo-Saxon Literature and Culture examine visual and textual representations of Jews, the translation and interpretation of Scripture, the use of Hebrew words and etymologies, and the treatment of Jewish spaces and landmarks. By studying the "imaginary Jews" of Anglo-Saxon England, they offer new perspectives on the treatment of race, religion, and ethnicity in pre- and post-conquest literature and culture."--